Reliance Ibn-e-Hisham on the Unknown Poetry for The Basis to Nahwu: اعتماد ابن هشام علی أشعار غیر معروفة للاستشهاد النحوی - Ahmad, Dr. Matloob; Saleem, Dr. Mufti Muhammad; Hasnain , Mubashar (Al Khadim Research Journal of Islamic Culture and Civilization, 2024)
This paper discusses “Reliance Ibn-e-Hisham on the unknown poetry for the basis to Nehvu” As it is well known that poetry is the foundation of nahwu experts in concluding the law, so that one of the foundations of this nahwu is found in many of their works. Although nahwu experts agree that poetry is one of the agreed upon foundations, they still limit the time and place, so they are reluctant to use except for poetry that comes from certain qabilah and in the istisyhaad era, namely the period between the pre-Islamic era to the beginning of the Abbasid dynasty. As for the period after that, they call their poets muwalladiin or muhdatsiin whose poems cannot be used as a basis. If the use of muwalladin's poems is prohibited, then of course, poems whose speakers are not known are more prohibited because they may come from people whose eloquence is not trusted. And this paper aims to reveal the extent to which nahwu experts obey these rules. And we take Ibn-e-Hisham Al-Anshary as an example in two of his books: syarhu qathri al-nadaa wa balli al-shadaa and syarhu syudzuuru al-dzhahab. And by using the descriptive analysis method, we find that Ibn Hisham in several places in these two books uses muwalladiin poetry and poetry whose speakers are not known as the basis for determining the law of nahwu.